Gluten cross contact in oats: retrospective database analysis 2011 to 2023 - Thompson, Tricia; Keller, Amy (Frontiers in Nutrition, 2023)
It is established that oats are at substantial risk for cross contact with gluten-containing grain. Specially processed gluten-free oats, whether purity protocol or mechanically sorted, made it possible for this grain to be included in a gluten-free diet in the U.S. Gluten Free Watchdog (GFWD) (U.S.) has been assessing the gluten content of labeled gluten-free foods since 2011. In 2022, there was an apparent increase in the number of oat products testing with quantifiable gluten >/= to 5 mg/kg. The purpose of the present study was to assess the levels of gluten in foods containing oats to identify any trends. In this retrospective database analysis, GFWD product test reports from April 2011 to May 1, 2023 were searched using the term “oat.” The search identified 213 individual packages of food that contained the word “oat” in the ingredients. Test results for these packages of food were reviewed. Of these, 24 (11%) tested with quantifiable gluten >/= to 5 mg/kg. The percentage of oats testing with quantifiable gluten varied per year but spiked in 2022 at 35%. It isn't possible to know for certain what caused this increase. The drought during the oat growing season of 2021 could be a major factor. One limitation of this study is that it was a retrospective analysis. Different numbers of oat products were tested each year and these were often different brands and formulations of oats. To assess the level of gluten cross contact in oats going forward a large prospective study is needed.